Continuity Of Care In Ny. L 29 th G1P0A0 at Publik Health Care Batealit Jepara - Emy Susilawati; Ely Mujianti; Putri Rahma Dini (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2023)
One of the programs the Central Java Provincial Government to reduce MMR and AKB which is relatively high is the One Student One Client (OSOC) program. The implementation of the One Student One Client (OSOC) program that uses the Continuity Of Care approach which is a series of continuous and continuous and comprehensive service activities. The method used in the Care of this Final Project Report is in the form of a case study using Varney's 7-step midwifery management approach and the form of SOAP. The results obtained are a case study on Mrs. L with during the postpartum period, care is given according to the needs of the mother, The conclusion from the results of this case study is that there are several gaps between theory and practice in the field, according to the situation and conditions in the field, is adjusted to the SOP that has been set.